Universal human rights norms and Islamic law: a case study of interpretation and definition of the principle of equality in Afghanistan between genders under the Taliban regime - Lēnerte, Danuta (Riga Graduate School of Law, 2024)
In a way, human rights are a reminder that puts pressure on humankind as a whole, to remember that all of us share the right to demand that human beings have equal rights. Thus, the principle of equality is the essence and a building block of human rights law. The principle is well defined, yet the struggle to understand it does not leave humankind. To address this, the present research delves into the essence of the principle within international human rights law and Islamic law. The analysis addresses the theoretical background of the principle as well as the origins of human rights. A comparison is made of its application between international human rights law documents and Islamic law. The thesis explores whether the unequal and discriminatory treatment towards women in Afghanistan under the Taliban regime is based on a misguided understanding of religious texts preached by the group, or whether there is a possibility that the holy book of Islam, together with other legal documents indeed preaches unequal treatment and a conflicting definition of international human rights law between sexes. The carried-out analysis based on the case studies done brings new light on the interpretation and meaning of the principle between two actors, as the threat of protecting women's rights and their equality becomes a more pressing issue in various countries, including Afghanistan, in today’s geopolitical turmoil.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; Religious law; Islamic law; International Bill of Human Rights; Afghanistan